Penegakan Hukum Pedata terhadap Pencemaran Lingkungan Hidup akibat Kegiatan Penambangan - Henry Nadiansyah Agustin; Neni Ruhaeni (UPT Publikasi Ilmiah Unisba, 2024)
ABSTRACT: Indonesia has established the function of environmental protection in the Environmental Protection and Management Law (UUPLH). Environmental management includes planning, utilization, control, maintenance, supervision and law enforcement. The main priority of this management is to prevent pollution and damage caused by human activities that exceed environmental standards, such as air, air and soil pollution, as well as damage to habitats and ecosystems. Environmental damage caused by human activities that exceed the carrying capacity of the environment can result in economic and social losses for society. Like nickel mining by PT. Various mines in the Mandiodo Block, North Konawe Regency, Southeast Sulawesi, have caused environmental pollution. The Ministry of Environment and Forestry (KLHK) discovered air and land pollution in the area in 2022 due to nickel mining activities that did not comply with environmental standards. This mining activity has caused the loss of people's livelihoods, the conversion of agricultural land to mining land, and pollution of sea waters. This research aims to determine civil law enforcement regarding environmental pollution due to mining waste which pollutes the air and land by PT Aneka Tambang in the Mandiodo Block and civil law enforcement regarding environmental pollution due to mining activities based on the Environmental Protection and Management Law (UUPLH) and Mineral and Coal Law (UU MINERBA) by PT Aneka Tambang in the Madiodo Block, North Konawe, Southeast Sulawesi. This research uses normative juridical legal research with qualitative analysis methods which are described descriptively using secondary data obtained from library study data collection methods in the form of primary legal materials, secondary legal materials and tertiary legal materials. Based on the research results, it is known that environmental law enforcement due to mining waste polluting the air and land by PT Aneka Tambang in the Mandiodo Block is by providing administrative sanctions against perpetrators of pollution and the victims have the right to compensation both material and non-material. In relation to civil law enforcement against environmental pollution in the practical settings in the Mandiodo Block, it is known that it has not been effective and that many environments are still polluted due to mining activities, causing local communities to lose their livelihoods. Law enforcement should aim to realize the wishes of the law, but in this case the community has not received justice because there is no support from any component of legal force. The existence of absolute responsibility towards UUPLH is expected to ensure that pollution victims receive compensation without requiring proof of fault and encourage violators to apply the precautionary principle in accordance with Article 88 of UUPLH. ABSTRAK Undang-Undang Perlindungan dan Pengelolaan Lingkungan Hidup (UUPLH) mengatur pengelolaan lingkungan melalui perencanaan, pemanfaatan, pengendalian, pemeliharaan, pengawasan, dan penegakan hukum untuk mencegah pencemaran dan kerusakan ekologis. Kasus pencemaran akibat penambangan nikel oleh PT Aneka Tambang di Blok Mandiodo, Konawe Utara, menimbulkan dampak serius seperti pencemaran udara, tanah, dan air, serta hilangnya mata pencaharian dan konversi lahan pertanian. Penelitian ini bertujuan mengkaji penegakan hukum perdata terkait pencemaran lingkungan dari limbah tambang menggunakan pendekatan yuridis normatif dengan metode kualitatif. Hasil penelitian menunjukkan penegakan hukum belum efektif. Banyak wilayah tetap tercemar, memengaruhi mata pencaharian masyarakat. Korban pencemaran berhak atas kompensasi tanpa pembuktian kesalahan, sebagaimana diatur dalam UUPLH. Namun, lemahnya dukungan otoritas hukum menghambat keadilan bagi masyarakat terdampak. Memperkuat penegakan hukum menjadi hal krusial untuk memastikan kepatuhan dan perlindungan lingkungan secara efektif. Upaya ini juga diperlukan untuk mengurangi dampak pencemaran dan memberikan keadilan bagi masyarakat terdampak.